O viaţă alături de Ovidiu Papadima - Ştefania Papadima (Revista de Istorie și Teorie Literară)
he memories of the author introduce us in the intimate family life of professor Ovidiu Papadima. Total unknown issues about the human being, his studies and his intellectual concerns are revealed.